Monitoring of A 1 kWp UiTM solar photovoltaic (PV) system / Mohd Firdaus Malek - Malek, Mohd Firdaus (2008)
A 1 kWp 'stand alone' PV system has been set up on January 2007 in Faculty of Electrical Engineering UiTM Shah Alam. This system consists of 4 module ( 2 BP SX75U module and 2 BP 275F module), inverter, 2 thermocouple, 3 voltage sensor, 3 current sensor,4 battery and data logger (Data Taker DT80). The main objective of this research is to monitor a 1 kWp UiTM solar photovoltaic (PV) system. The specific objective of this research is to design, develop and test the photovoltaic monitoring system. This research involve nine parameters which are irradiance (Ia), ambient temperature (Tamb), module temperature (Tmod), module voltage (Vmo<j), battery voltage (Vbat), load voltage (Vioad), module current (Imod), battery current (Ibat) and load current (Iioad)- All parameters were measured using the equipments and sensors that connected directly to data logger (Data Taker DT80) to interpret and show the data on computer using the Delogger sofware. This research was done for 2 weeks from 14 March 2008 to 27 March 2008. The data was taken for every 10 minutes time interval everyday in 24 hours. The data then was transferred into the computer and analyzed using the Deview and Microsoft Excel software to determine the performance indices for the stand alone PV system. From the analysis a few performance indices were determined. The range of daily solar irradiation is between 2.20 kWhm"2 to 4.00 kWhm"2, while the range of total global irradiation is between 5.76 kWh to 10.48 kWh. For daily total energy yield, the range is between 0.23 kWh d"1 to 0.28 kWh d"1. The range for clearness index is between 0.49% to 0.89%. The range for final yield is between 0.77 kWh d"1 kWp"1 to 0.93 kWh d'1 kWp _1 while the range of array efficiency is between 2.53% to 4.65%. Lastly, the range of the performance ratio is between 22.08% to 40.58%.